(untitled) (Scientific journal of the Fergana State University, 2025)
Using various types of animal manure, food waste, hay, straw, and other nutrient substrates common in Uzbekistan, high-quality biohumus fertilizer was obtained, fully meeting international standards. Compared with biohumus produced abroad (Russia, Ukraine, Belarus), the obtained biohumus contains 3-5% more humus, 0.2-0.3% more potassium and nitrogen, 4% more ash, the same amount of phosphorus, and 16 additional microelements (which were absent in local biohumus). Additionally, it was shown that 1 mm³ of biohumus contains vitamins, biostimulants, and 2.5-3 billion microorganisms. It is known that the composition of humus depends on the composition of the substrate consumed by worms: manure from animals fed with concentrated feed is rich in organic matter and allows for the production of high-quality biohumus. For this reason, the most suitable nutrient medium was selected for worm breeding.